Pricing strategies of the tobacco companies in response to cigarette excise tax increases in Montenegro - Mirjana Čizmović; Ana Mugoša; Milica Vukčević; Violeta Vulović (PLoS ONE, 2026)
This study examines the impact of excise tax increases on cigarette prices in Montenegro, offering insights into the tobacco industry’s pricing strategies. Using both panel quantile regression and fixed-effects models, the research estimates excise tax pass-through to cigarette prices across different price ranges and market segments. The analysis is based on monthly price data from 2010 to 2022 for 269 cigarette brands. The findings reveal partial tax pass-through for lower-priced brands, while premium brands experience over-shifting, meaning tax increases are more than fully passed on to consumers. Slim cigarettes remain relatively affordable, as their prices never fully reflect tax increases. This pricing strategy allows the industry to maintain a substantial price gap between premium and low-cost cigarettes while sustaining profitability. Industry-driven cross-price subsidies for low-cost cigarettes undermine the intended impact of excise tax increases by maintaining their affordability and consumption. This highlights the need for comprehensive reforms in Montenegro’s tobacco tax policy to ensure effective tobacco control.